PERAN UNIVERSITAS DALAM PENGUATAN IDENTITAS BAMBU DI KABUPATEN TANGERANG MELALUI LOMBA VIDEO PENDEK - Fitri Anisa Kusumastuti; Muh. Khaedir Lutfi (JURNAL PENGABDIAN KEPADA MASYARAKAT SERUMPUN MENCIPTA, 2025)
The use of bamboo as part of the cultural identity of Tangerang Regency has begun to decline due to the development of industry and the property sector. Universities have a strategic role in supporting the development of culture and creative economies based on local wisdom. One of the real forms of contribution from Universitas Tangerang Raya is through participation in the Tangerang Regency Video Competition with the theme of strengthening bamboo identity. This competition aims to increase public awareness of the importance of bamboo in social, economic, and cultural life. This article discusses the active role of universities in this activity, including socialization, training, mentoring participants, and academic contributions in the documentation and publication of competition results. The results of the study show that university participation has a positive impact on increasing community and student involvement in raising local potential through creative media.